Design Adventure Role Playing Game with Procedural Content Generation using Perlin Noise Algorithm - Raul Andrian; Angga Aditya Permana; Adhi Kusnadi (Universitas Pradita, 2022)
Producing quality video game content is not easy. In the process of creating game content, it will require a lot of resources, a long time and expensive costs. This problem can be solved by applying the Procedural Content Generation or PCG method to create game content using certain algorithms without having to create it manually. In this study, the Perlin Noise algorithm was used to create a map for the game that was built. This research was made with the aim of designing and building an Adventure RPG game using the Perlin Noise algorithm, as well as measuring the level of player satisfaction with the game that has been made. The game engine used in the process of making this game is the 2019 version of Unity Engine 3D with the C# programming language on the windows platform. After the game creation process is complete, it will be continued by testing using the Game User Experience Satisfaction Scales 18 (GUESS-18) method which provides 18 questions to measure the level of player satisfaction with games built with PCG. Based on the results of the tests that have been carried out, the final result with a value of 81,85 % indicates that the game that has been successfully built is included in the good predicate category.